Pengembangan Macromedia Flash Dalam Pembelajaran Kimia Pada Materi Ikatan Kimia Untuk Meningkatkan Minat Belajar Siswa - Elferida Sormin; Rosmelia Daeli (EduMatSains : Jurnal Pendidikan, Matematika dan Sains, 2018)
This study aims to determine: the effect of the use of Macromedia Flash to student interest. The population in this study were high school PSKD 7 Depok and Sample in this research were students of class XI-IPA SMA PSKD 7 Depok academic year 2016/2017. Data collection tool used in this study is the use of a questionnaire pre-test and post test with purposive technique. Collecting data using a questionnaire to collect data on students' perceptions of learning macromedia flash media usage data and student interest. Test requirements have been carried out in the form of normality test, test Homoegnitas, Hypothesis Testing with SPSS 2.0 for windows and Analysis of the data used in this study is a Likert Scale Test. The results of data analysis showed there was a positive influence among student interest in the use of learning media. Based on data analysis and hypothesis testing are carried out found that: (1) There is an increased interest of students of class XI-IPA SMA PSKD 7 Depok FY 2016/2017 in the matter of chemical bonds using Macromedia Flash it can be seen from the total score in the category Likert scale strongly agree (total score of 2603) and the data is normally distributed with sig> 0.05 and homogeneous with sig> 0, 05. (2) The percentage interest of students in chemical bonding materials increased by 18% after using Macromedia Flash. Keywords: Instrucsional Media, Learning nteresting, Macromedia Flash.